Financial Flexibility and Investment Efficiency : Based on the Empirical Data of Listed Companies in the New Generation of Information Technology Industry - SUN, SISI (Pacific International Journal, 2023)
In recent years, the external financing environment of enterprises has deteriorated, especially since the impact of the COVID-19 epidemic, which has further limited external financing opportunities for enterprises. Therefore, it is imperative to adopt effective financial strategies to promote enterprise growth. This paper examines the influence mechanism of financial flexibility on the investment efficiency of new generation listed companies in the information technology industry from 2017 to 2020. Using the adjustment path analysis method, the paper constructs and verifies the role path of "financial flexibility → investment efficiency" to explore the impact of financial flexibility on investment efficiency and its effect on enterprise growth. The status quo of financial flexibility and investment efficiency of listed companies in the new generation of information technology industry is analyzed descriptively using stata16.0 statistical software. The paper proposes a hypothesis and constructs a multiple linear regression model to examine the influence of financial flexibility on investment efficiency. The empirical results show that the new generation of IT enterprises face challenges such as low capital flexibility and investment efficiency, particularly insufficient investment. Financial flexibility can help enterprises cope with capital demands under uncertain circumstances and improve the efficiency of enterprise investment. Therefore, in the market environment, enterprises should retain financial flexibility while strengthening internal control to improve investment efficiency and meet the needs of enterprise growth. The government and financial sector should promote supply-side structural reform in the financial sector, raise the level of regional financial development, and provide a favorable environment for external financing of strategic emerging industries such as the next-generation information technology industry.